2020
DOI: 10.1177/2040620720958586
|View full text |Cite
|
Sign up to set email alerts
|

High CXCR2 expression predicts poor prognosis in adult patients with acute myeloid leukemia

Abstract: Aims: This study aimed to assess the associations between clinical parameters, long-term outcomes, and expression of chemokine receptor CXCR2 in patients with acute myeloid leukemia (AML). Methods: From May 2013 to May 2017, 83 adult patients newly diagnosed with AML in the Affiliated Hospital of BeiHua University and Jilin Chemical Hospital, were enrolled in this study. The expression of CXCR2 in bone marrow mononuclear cells was determined by quantitative real-time polymerase chain reaction (qRT-PCR). Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This increase of CXCR2 ligands is also observed for other types of cancers [ 9 , 44 , 45 ]. Moreover, we have recently shown that CXCR2 levels were also increased in human TNBC compared to luminal breast tumors [ 13 ], as shown for other types of cancers [ 46 , 47 , 48 , 49 ]. We find that Cxcr2 ablation leads to an increase of both primary tumor growth and the development of lung metastasis.…”
Section: Discussionmentioning
confidence: 83%
“…This increase of CXCR2 ligands is also observed for other types of cancers [ 9 , 44 , 45 ]. Moreover, we have recently shown that CXCR2 levels were also increased in human TNBC compared to luminal breast tumors [ 13 ], as shown for other types of cancers [ 46 , 47 , 48 , 49 ]. We find that Cxcr2 ablation leads to an increase of both primary tumor growth and the development of lung metastasis.…”
Section: Discussionmentioning
confidence: 83%
“…CXCR2 has significant pro-tumor functions, where increased CXCR2 expression is associated with poorer patient prognosis, as shown by studies on acute myeloid leukemia [101], invasive ductal breast cancer [102], colorectal cancer [103], esophageal cancer [104], gastric cancer [16,17,105,106], intrahepatic cholangiocellular carcinoma [107], laryngeal squamous cell carcinoma [108], lung adenocarcinoma [109], non-small cell lung cancer [91], ovarian cancer [110,111], pancreatic ductal adenocarcinoma [112]. In contrast, in studies on triplenegative breast cancer [113], colorectal cancer [114], clear cell renal cell carcinoma [115], gastric cancer [116] and pancreatic ductal adenocarcinoma [117] (Table 1), no such association is shown, which may be related to the initiation of an antitumor immune response resulting in tumor infiltration by tumor-infiltrating lymphocytes (TILs), in particular CD8 + cytotoxic lymphocytes [113].…”
Section: The Role Of Cxcr2 In Cancermentioning
confidence: 97%
“…To identify potential major regulators along with their subgroup-specific expression behavior, we learned gene regulatory networks associated with the observed expression changes between the three T-PLL subgroups ( Fig 6 ). Most of the 41 revealed genes with increased network connectivity have been reported to be involved in different types of cancer and several of them have been shown to be important in different types of leukemia ( Table 1 , ALPP [ 34 ], AHSP [ 44 ], CXCL8 [ 37 ], CXCR2 [ 47 ], ELANE [ 53 ], FFAR2 [ 40 ], G0S2 [ 38 ], GIMAP2 [ 55 ], IL1RN [ 39 ], LCN2 [ 36 ], MBTD1 [ 51 ], PPP1R15A [ 49 ]). Thus, it is likely that at least some of these genes may also contribute to T-PLL development and that their subgroup-specific expression behavior may contribute to the globally observed gene expression differences of the T-PLL subgroups.…”
Section: Discussionmentioning
confidence: 99%